CHARACTERISTICS OF CHILDREN AGE OF BASIC EDUCATION - Mutia (FITRAH: International Islamic Education Journal, 2021)
Education aims to gain knowledge and all activities that affect a person's strength, change, character and morals. The period of childhood education to a young age goes through various and changing stages. The childhood phase begins with the beginning of the first three years, the fourth year to the sixth year, the sixth year to the eighth year, the eighth year to the twelve year. Characteristics of children of basic education age are happy to play, move, work in groups and like to demonstrate things directly. In childhood, developmental and educational disorders often occur, namely learning disorders, dyslexia, dyscalculia, and dysgraphia. Thus understanding the characteristics of children is a must for teachers and parents to be able to educate and guide children in a better direction.